## Solve by elimination: 3x = y + 5, 5x – y = 11

Question

Solve by elimination: 3x = y + 5, 5x – y = 11

in progress 0
1 week 2021-11-19T18:28:08+00:00 2 Answers 0 views 0

x = 3 and y = 4 and here’s the step by step explained below

Step-by-step explanation:

Given a pair of linear equations such that,

3x = y + 5 ..(1)

5x – y = 11 .(2) To solve it by substitution method.

Fron eqn (1), we have, => y = 3x -5

Now, substituting this value in eqn (2), we get

=> 5x -(3x-5) = 11 => 5x – 3x +5 = 11

=> 2x = 11-5

=> 2x = 6

=> x = 6/2

=> x = 3

Therefore, we have,

=> y = 3(3) – 5 =

=> y = 9-5

=> y = 4

Hence, the values of x= 3 and y = 4.

hope u like plzz mark it as brainliest plzz bro

according to the question,

3x = y + 5 ..(1)

5x – y = 11 .(2)  by substitution method.

Fron eqn (1), we have, => y = 3x -5

Now, substituting this value in  2

5x -(3x-5) = 11 => 5x – 3x +5 = 11

2x = 11-5

2x = 6

x = 6/2

x = 3

so we will have

y = 3(3) – 5 =

y = 9-5

y = 4

therefore  the values of x= 3 and y = 4.